ANALISIS WACANA POLITIK KABAR PEMILU DALAM YOUTUBE CHANNEL TVONENEWS: KAJIAN PRAGMATIK - Wulandari S.; Yesi Pramudita (STKIP Paris Barantai, 2025)
The purpose of this study is to describe the analysis of political discourse on the YouTube channel Kabar Pemilu. The method used in this study is descriptive with a qualitative approach. This method describes the data presented in the form of words that contain the meaning of the research results. The techniques used in data collection include observation, listening techniques, reading techniques, writing techniques, analysis techniques, documentation, and triangulation. The data analysis techniques used in this study include data collection, data reduction, data presentation, and drawing conclusions. Based on the research results